In vitro effects of growth regulators on proliferation of shoots of M-7 apple rootstock - Yui, Edson; Pasqual, Moacir; Ramos, José Darlan; Nagig, Nilton; Chalfun, Jorge; Ishida, Jorge Susumu (Pesquisa Agropecuaria Brasileira, 1993)
The objective of this work was to research the effect of different concentrations of 6-benzylaminopurine (BAP), naphthalene acetic acid (ANA) and gibberellic acid (GA3) on the in vitro multiplication of apple tree rootstock M-7. In this experiments, all possible combinations between BAP (0,0; 0,5; 1,0; 2,0; and 4,0 mg/l) and GA3 (0,0; 0,01; 0,1 and 1,0 mg/l); between BAP (0,0; 0,5; 1,0; 2,0 and 4,0 mg/l) and ANA (0,0; 0,001; 0,01 and 0,1 mg/l); and between GA3 (0,0; 0,01; 0,1 and 1,0 mg/l) and ANA (0,0; 0,001; 0,01 and 0,1 mg/l) were tested. The explants (segments of shoots with 1,0 cm of length) were inoculated (one/tube) and cultured at 27 ± 2°C, 16 hr photoperiods and 3,000 lux light intensity. The evaluation was made after 28 days through total number of branchs higher than 1,0 cm. The in vitro multiplication can be made successfully using 0,5 and 2,0 mg/l of concentration. The ANA and GA3 are dispensable.